Persistence of Results of Open Pension Funds/OFE Operating on the Polish Capital Market during the Pandemic - Kurzyk, Beata (Journal of Finance and Financial Law, 2024)
The purpose of the article. Demonstrating the repeatability of pension fund performance is an important indicator of future investment decisions. Research on the persistence of results was and still is mainly focused on investment funds. In Poland little research has been devoted to the issue of maintaining the performance of pension funds, minimal in relation to OFE. The main aim of this paper was to examine the persistence of OFE results on the Polish capital market during the pandemic Covid-19. Methodology. Ten OFE funds were identified. The analysis covered the persistence of rates of returnof individual OFEs, calculated at monthly (34), quarterly (11), and half-yearly (5) intervals in the period from March 1, 2020 to December 31, 2022. The analysis was carried out using a measure whose structure is based on rate of return calculated based on the reference rate (risk-free excess rate of return). Results of the research. The article presents the results of research on the persistence of return rates of ten Open Pension Funds in Poland during the COVID-19 pandemic. The results were shown to be inconsistent and reversible. This speaks in favor of the hypothesis that short-term repetition does not occur during economic downturns.